Answer:
![\lim_(x \to 0)\ x^2 -2 = -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bkr72k31cc339a34b7bhddksaghranxnr0.png)
Explanation:
We have the following limit
![\lim_(x \to 0)\ x^2 -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2y7ezvy1vnm68evhplxyj6p9a7blpm316o.png)
To solve this limit using direct substitution to substitute the value that tends x into f(x) and simplify.
In this case x tends to zero, then we substitute x = 0 in the function and simplify
![\lim_(x \to 0)\ x^2 -2= (0)^2 -2= -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cqbwfxkbco4qjklcu29byo6g7aqyms0i2w.png)
Therefore
![\lim_(x \to 0)\ x^2 -2 = -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bkr72k31cc339a34b7bhddksaghranxnr0.png)
When x approaches 0 then f(x) it tends to -2